2005
DOI: 10.1111/j.1600-051x.2005.00658.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of improved periodontal health on metabolic control in type 2 diabetes mellitus

Abstract: The results of our study showed that non-surgical periodontal treatment is associated with improved glycaemic control in type 2 patients and could be undertaken along with the standard measures for the diabetic patient care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

35
341
5
21

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 316 publications
(402 citation statements)
references
References 58 publications
35
341
5
21
Order By: Relevance
“…This result is in agreement with various other studies [51,52]. This result may be due to the fact that patients with well-controlled diabetes mellitus might respond to non-surgical therapy similarly well as healthy controls [48] and many of the patients in this study were controlled, diabetic patients.…”
Section: Latha Et Alsupporting
confidence: 82%
See 1 more Smart Citation
“…This result is in agreement with various other studies [51,52]. This result may be due to the fact that patients with well-controlled diabetes mellitus might respond to non-surgical therapy similarly well as healthy controls [48] and many of the patients in this study were controlled, diabetic patients.…”
Section: Latha Et Alsupporting
confidence: 82%
“…There was no significant difference in FBS value in Group 2. This is in agreement with a study by Grossi et al [49] and Kiran et al [52] who concluded that elimination of periodontal infection and improvement of periodontal inflammation significantly reduces the level of HbA1c in the short term, hence, improving diabetes metabolic control. Stewart et al [51] reported a reduction in HbA1c value from 9.5% to 7.6% 10 months following non-surgical therapy.…”
Section: Latha Et Alsupporting
confidence: 82%
“…Age is a significant factor for periodontal disease, as the prevalence of periodontal disease increases rapidly with age and also most people with type 2 diabetes belong to this age group [23,24]. This age range is in accordance with other studies [25,26].…”
Section: Non-surgical Periodontal Therapy (Srp)-effect On Glycaemic Csupporting
confidence: 78%
“…30 Clinical studies have demonstrated that improvement in metabolic control correlates with improvement in periodontal health. 15,31,32 However, in the current study, while the improvement in the periodontal condition observed in those with DM had some the study, so the obtained effect might simply be a result of the periodontal treatment.…”
mentioning
confidence: 51%